Manajerial Supervisi Akademik Pengawas, Kepala dan Guru Sekolah dalam Rangka Peningkatan Kompetensi Pedagogik di Raudhatul Athfal - Lilis Lisnawati; Arfiani Yulianti Fiyul; Yurna Yurna (Institut Madani Nusantara, 2021)
Education is a process that is done to turn people who do not know to know, we need to know that the purpose of education is to create someone of quality and character so that they have a broad view in the future to achieve an expected goal and be able to adapt quickly and precisely in various environments. But on the way, of course education can't go it alone. The existence of suvervisi to improve the quality of education, also managerial of the headmaster in order to run well, and Teachers as the spearhead in the field to be able to carry out pedagogical competencies in all students. In addition, the research led to 1) supervision planning of supervisors, principals, and teachers in improving pedagogical competencies of Raudhatul Athfal. 2) Implementation of supervision of supervisors, principals, and teachers in improving pedagogical competencies in Raudhatul Athfal. 3) Evaluation of the supervision of supervisors, principals, and teachers in improving the competence of peadagogik Raudhatul Athfal. 5) Supporting factors and inhibitions in the study.